Speed-Sensorless Stator Flux-Oriented Control of Induction Motor Drives in Traction - Manfred Depenbrock; Andreas Steimel; Christian Foerth; Frank Hoffmann; Markus Weidauer; Stefan Koch (Communications - Scientific letters of the University of Zilina, 2001)
Indirect Stator-Quantities Control (ISC) combines the principle of stator flux-orientation proven successful in Direct Self Control (DSC) with Pulse Width Modulation (PWM). High torque dynamics and robust behavior against input voltage disturbance are achieved in the whole operation range including field-weakening. After careful correction of inverter voltage errors the difference of the stator current space vectors in the machine and in the control model is employed for speed estimation, allowing dispensing with speed sensors. A special flux management allows an infinitely slow change between driving and braking.